2021
DOI: 10.1186/s12902-021-00863-x
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between high-density lipoprotein cholesterol (HDL-C) and glycosylated hemoglobin in diabetic patients aged 20 or above: a cross-sectional study

Abstract: Aim The incidence rate of diabetes is increasing year by year, seriously threatening human health. As a predictor of glycemic control, glycated hemoglobin is reported to be related to various complications and prognoses of diabetes. Besides, HDL-C dyslipidemia is a component of metabolic syndrome and may be related to various cardiovascular and cerebrovascular diseases. The principal objective of this project was to investigate the relationship between HDL-C and glycosylated hemoglobin in adult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 35 publications
1
8
0
Order By: Relevance
“…Moreover, HDL‐C amplifies insulin receptors in muscle cells by activating GLUT‐4, which facilitates glucose uptake by these cells (van Linthout et al., 2010 ). Furthermore, HDL‐C and HbA1c levels demonstrate an inverse correlation, as reduced HDL‐C levels are associated with reduced glucose homeostasis (Huang et al., 2021 ; Maharjan et al., 2017 ). HbA1c originates from an irreversible Schiff base reaction in which glucose molecules bind to the N‐terminal end of the β ‐globin chain of hemoglobin.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, HDL‐C amplifies insulin receptors in muscle cells by activating GLUT‐4, which facilitates glucose uptake by these cells (van Linthout et al., 2010 ). Furthermore, HDL‐C and HbA1c levels demonstrate an inverse correlation, as reduced HDL‐C levels are associated with reduced glucose homeostasis (Huang et al., 2021 ; Maharjan et al., 2017 ). HbA1c originates from an irreversible Schiff base reaction in which glucose molecules bind to the N‐terminal end of the β ‐globin chain of hemoglobin.…”
Section: Discussionmentioning
confidence: 99%
“…26 A previous cross-sectional study found that HDL-C is inversely associated with HbA1c and may be relevant to glycemic control in patients with diabetes. 27 The carotid IMT, as a noninvasive marker of atherosclerosis, can predict the risk of cardiovascular disease, and increased IMT is linked to an increased risk of subsequent cardiovascular events. 28,29 UHR as a biomarker for evaluating inflammatory status was found to be positively associated with incident heart ischemia incidence in Koreans without diabetes.…”
Section: Discussionmentioning
confidence: 99%
“… 26 A previous cross-sectional study found that HDL-C is inversely associated with HbA1c and may be relevant to glycemic control in patients with diabetes. 27 …”
Section: Discussionmentioning
confidence: 99%
“…Dyslipidemia has been suggested to have a linear relationship with HbA1c in recent studies, and HbA1c could reflect cholesterol and LDL levels among T2DM patients. A marked increase for TC and TG levels and a decrease for HDL-C levels compared to patients with good glycemic control [ 21 23 ]. For most patients with DM, the better the glycemic control, the more likely they are to exhibit a more active and healthy lifestyle that leads to better management of lipid levels [ 17 ].…”
Section: Discussionmentioning
confidence: 99%